ANALISIS RISK & RETURN PADA BUMN SEKTOR INDUSTRI JASA TELEKOMUNIKASI DI JAKARTA - Buchary jaja (Media Riset Bisnis & Manajemen, 2002)
The main purpose of this research is to detemine whether Retum (ROE, EPS, and Rentatibility) which is produced by Telecommunication Service Industry's BUMNS, was mentioned before, increases because of the increasing of Risk (Financial Leverage) used. There will be an analysis and comparison of both BUMNS to describe this relationship and the effect of the Risk (Financial Leveraging) to Retum (ROE, EPSand Rentatibility). The analysis includes the effects of each BUMN, the strength or weakness relationship of both BUMN to the effect in Risk (Fianncial Leveraging) and Return (ROE, EPS and Rentatibility). The objects of this research are all BUMNS in Telecommunication Service Industry that has gone public and has five years stated financial report from 1992 to 1996.